Adolescente de 15 años de edad con anemia ferropénica - Morales Barragán, Ingrid Thalia (2018)
Ferropenic anemia in adolescents of 15 years old, is one of the most common pathologies, is caused by inadequate intake, increased requirements, chronic losses among others, it can be confused with other pathologies due to its clinical manifestations such as dyspnea, headache, dizziness, weight loss; it differs from other types of anemia, due to the deficiency of hemoglobin, hematocrit and red blood cells. In the present clinical case it was observed that the treatment employed gave a positive result by a treatment with iron 2 drinkable ampoules, complex b, plus a diet rich in iron. Through periodic visits, the adolescent was observed who collaborated in a positive way for his recovery. Follow-up was done to adolescents for the period of three months. Each month a hemogram was performed and favorable changes were observed in hemoglobin values, in the first month 9.8 g / dl and hematocrit of 37% and red blood cells 4200000cc, second month of 10.3 g / dl hematocrit of 38% and red blood cells 4600000cc third month of 10.9 g / dl hematocrit of 39% and red blood cells 5 000000cc.